PGP Attributes of Non-rhizobial Bacterial Endophytes from Root Nodules of Wild Leguminous Plant Tephrosia Purpurea (L) Pers. - Harshita Vashistha; Prashant Kumar; Sandeep Kumar (Environment Conservation Journal)
Global agriculture practices rely heavily on the application of fungicides, pesticides and synthetic fertilizers. Several bacterial strains were isolated from root nodules and screened for plant growth-promoting (PGP) activities. The selected isolates were characterized biochemically and identified by 16S rRNA sequencing. The ability of bacterial isolates to produce siderophores, phosphate solubilization, production of indole acetic acid (IAA) and other characteristics of plant growth promoting (PGP)activities were evaluated from the root nodules of a wild leguminous plant, Tephrosia purpurea (L.) Pers. Based on the results, the isolates were determined as Bacillus altitudinis and Pseudomonas azotoformans. The bacterial consortium consisting of B. altitudinis + P. azotoformans exhibited a substantial enhancement in both root length (35.55%), and shoot length (43.2%) when compared to the control. This study concludes that utilization of the beneficial traits of these non-rhizobial nodule endophytes bacteria improve nodulation biomass accumulation and plant vegetative growth parameters in T. purpurea. The present research has the potential to advance the adoption of eco-friendly agricultural practices and provide an alternative substitute for traditional chemical fertilizers.